Structural Parameter Design of Magnetic Pulse Welding Coil for Dissimilar Metal Joints: Numerical Simulation, Parameter Optimization, and Experiments - Yangfan Qin; Changhui Ji; Hao Jiang; Yuefan Jiang; Junjia Cui; Guangyao Li (Machines)
As a main component of the magnetic pulse welding (MPW) system, the working coil exerts a great influence on the electromagnetic force and its distribution, which, in turn, affects the quality of the MPW joints. This study proposes a structural parameter optimization of the MPW coil, with the objective of achieving a higher induced current density on the flyer plate. The optimal Latin hypercube sampling technique (OLHS), Kriging approximate model, and the Non-Linear Programming by Quadratic Lagrangian (NLPQL) algorithm were employed in the optimization procedure, based on the finite element model built in LS-DYNA. The results of the sensitivity analysis indicated that all the selected parameters of the coil had a specific influence on the induced current density in the flyer plate. The optimized coil structure serves to refine the pulse current flowing path within the coil, effectively reducing the current loss within the coil. Additionally, the structure reduces the adverse effect of the current within the coil on the induced current within the flyer plate. Numerical results show the peak-induced current of the flyer plate increasing by 25.72% and the maximum Lorentz force rising by 58.10% at 25 kJ with the optimized coil structure. The experimental results show that with the same 25 kJ discharge energy, the optimized coil could increase the collision velocity from 359.92 m/s to 458.93 m/s. Moreover, 30 kJ of discharge energy should be needed to achieve the failure mode of base material failure with the original coil, while only 15 kJ should be applied to the optimized coil. These findings verify the optimization model and give some outline for coil design.